Probiotics in obstetric practice: efficacy and safety - Juliia E. Dobrokhotova; Ekaterina I. Borovkova (IP Berlin A.V., 2020)
The intestinal microbiota modulates immune programming and can prevent the realization of an allergic phenotype. For the formation of a normal microbiocenosis of the intestine, skin and oral cavity, a sufficient quantitative and qualitative bacterial colonization of the newborn is necessary during the transition from a sterile intrauterine environment to microbial colonization, resulting in the appearance of more than 1014 microorganisms. Low levels of bifidobacteria and early colonization of potentially pathogenic bacteria are associated with the development of severe allergic reactions. Prescribing probiotics containing Lactobacillus rhamnosus GG (LGG) at a concentration of 1081010 CFU from 36 weeks of gestation and during the first 34 months of lactation is associated with a 21% reduction in the risk of allergic reactions in the child.